POLA KOMUNIKASI KELUARGA, FUNGSI SOSIALISASI DAN BENTUK KOMUNIKASI YANG TERJADI DALAM KELUARGA DI PERMUKIMAN DAN PERKAMPUNGAN KOTA BEKASI - Sari, Afrina; Hubeis, Aida Vitayala; Saleh, Amiruddin (Makna: Jurnal Kajian Komunikasi, Bahasa, dan Budaya, 2010)
This research explains that family communications pattern, function of socialization, form of communication happened in family who live in setlement and family who live in countrified. Method which in using in this research is descriptive survey method and data in analysis applies Chi square (X²) statistical with program SPSS version 1600. Result of research indicates that family who live in setlement and family who live in more countrified tends to mengunakan family communications pattern Laissez-faire which in combination with family communications pattern pluralistik, pattern pluralistik in combination with pattern konsensual. Function of socialization at family who live in setlement is more usingly is active socialization and family who live in countrified more usingly is passive socialization. Form of communication verbal is more in using in countrified while family who live in setlement is more usingly is form of communication verbal and nonverbal.